Molecular and immunohistochemical analyses of BCL2, KI-67, and cyclin D1 expression in synovial sarcoma - Krsková, Lenka; Kalinová, Markéta; Brízová, Helena; Mrhalová, Marcela; Sumerauer, David; Kodet, Roman (Cancer genetics and cytogenetics, 2009)
Synovial sarcoma (SS) is a highly aggressive soft tissue sarcoma that causes death in more than half of the affected patients. An immunohistochemical and molecular study of the BCL2, MKI67, and CCND1 genes (expressing the BCL2, KI-67, and cyclin D1 proteins, respectively) was performed to determine the expression profiles in correlation with mRNA levels, and to assess the possible utility of these genes as a potential target for the treatment. Cyclin D1 staining was identified in 18 of 30 cases (60%), and CCND1 mRNA was overexpressed in 15 of 32 cases (47%). KI-67 nuclear immunoreactivity was found in 14 of 29 cases (48%), and MKI67 mRNA was overexpressed in 12 of 32 cases (37.5%). The high level of MKI67 mRNA was observed predominantly in monophasic SS. BCL2, a negative regulator of apoptosis, was expressed in all 32 cases. The intensity of the BCL2 protein expression correlated well with the mRNA level (P<0.0001). The high level of BCL2 mRNA correlated with a high level of CCND1 mRNA, but not with MKI67 mRNA level. Despite advances in therapy of sarcomas, the prognosis of patients with SS remains unfavorable, and a search for an improved therapy approach remains necessary. The strong immunopositivity of BCL2 in SS correlates well with a high level of BCL2 mRNA. Treatment with antisense BCL2 (G3139) may therefore represent an appropriate alternative therapy for patients with BCL2-positive synovial sarcomas.
Keywords: buněčné jádro; Humans; neparametrická statistika; Aged; Child, Preschool; Adolescent; RNA nádorová; dítě; senioři; Cell Nucleus; mladiství; synoviom; Ki-67 Antigen; Male; Child; předškolní dítě; lidé středního věku; Analysis of Variance; Statistics, Nonparametric; lidé; Adult; messenger RNA; mužské pohlaví; polymerázová řetězová reakce s reverzní transkripcí; Sarcoma, Synovial; Female; Immunohistochemistry; Cyclin D1; dospělí; RNA, Messenger; Middle Aged; analýza rozptylu; antigen Ki-67; Soft Tissue Neoplasms; ženské pohlaví; Infant; kojenec; Proto-Oncogene Proteins c-bcl-2; RNA, Neoplasm; cyklin D1; protoonkogenní proteiny c-bcl-2; nádory měkkých tkání; Reverse Transcriptase Polymerase Chain Reaction; imunohistochemie